Analysis of the Increase in Covid-19 Patients in Maluku Province Using Markov Chain Method - Rumata, Umi Sari; Lesnussa, Yopi Andry; Noya van Delzen, Marlon Stivo (Pattimura International Journal of Mathematics (PIJMath), 2022)
Since the beginning of 2020, most of the world has been hit by the covid-19 pandemic, patients who are confirmed to be covid-19 are increasing day by day until the end of 2020, this increase in covid-19 patients has also occurred in the province of Maluku. In this study using the Markov chain method to analyze the increase in COVID-19 patients in the Maluku province, the results of the study were obtained that there were 5 ranges of adding positive COVID-19 patients with the opportunity value of increasing in each range as follows In the range of 0-20 people, the opportunity value is 0.103, the range of 21-40 people, is the opportunity value 0.098, the range 41-60 people is the opportunity value is 0.093, the range 61-80 people is the opportunity value is 0.1, the range of more than 81 people the opportunity value is 0.74.